Service orientation winning strategies and best practices - Allen, Paul 1949- (Cambridge University Press, 2006)
Companies face major challenges as they seek to flourish in competitive global markets, fuelled by developments in technology, from the Internet to grid computing and Web services. In this environment, service orientation - aligning business processes to the changing demands of customers - is emerging as a highly effective approach to increasing efficiency. In this book, Paul Allen provides an accessible guide to service orientation, showing how it works and highlighting the benefits it can deliver. The book provides an integrated approach: after covering the basics of service orientation, he discusses key issues such as business agility, designing quality-of-service infrastructure, implementing service-level agreements, and cultural factors. He provides roadmaps, definitions, templates, techniques, process patterns and checklists to help you realize service orientation. These resources are reinforced with detailed case studies, from the transport and banking sectors. Packed with valuable insights, the book will be essential reading for CIOs, IT architects and senior developers. IT facing business executives will also benefit from understanding how software services can enable their business strategies. Paul Allen is a principal business-IT strategist at CA and is widely recognized for his innovative work in component-based development (CBD), business-IT alignment and service-oriented architecture. With over thirty years experience of large-scale business systems, he is an established author whose previous book was the critically acclaimed Realizing e-Business with Components. Sam Higgins is now with Forrester Research Inc.; formerly he managed the Innovation and Planning Unit of Queensland Transport's Information Services Branch. Paul McRae is the application architect in the Innovation and Planning Unit of Queensland Transport's Information Services Branch. Hermann Schlamann is a senior architect in the architecture group of Credit Suisse.